Draft Annual Plan 1973-74 Jammu and Kashmir State Vol I - Planning Commission (Planning Commission, 1972)
The state of Jammu and Kashmir with its very low per capita income is one of the poorest states in the country. According to the tentative estimates, formulated some time back, the per capita income in the State at 1955-56 prices was only Rs. 301 in 1970-71 against the national level of Rs. 347 the problems of the State arise out its geographical location and topographical difficulties. The mountainous terrain has loft many pockets of extreme backwardness in the State which itself has remained much below the economic level, attained in the rest of the country Agriculture in most parts of the State is limited to a single crop.
Jammu and Kashmir State
Jammu and Kashmir State
Keywords: Financial Resources; Agricultural Programmes Sector; Co-operation; Irrigation and Power Sector; Economic background; Power Development; Social Services; Review of financial and Physical Achievements; Centrally sponsored scheme; Gardens; Parks Floriculture; Sheep Husbandry; Land Reforms